EFFECT OF PROCESSING ON VITAMIN C CONTENT, TOTAL PHENOLS AND ANTIOXIDATIVE ACTIVITY OF ORGANICALLY GROWN RED BEETROOT (BETA VULGARIS SSP. RUBRA) - Pavlović, Nenad V; Mladenović, Jelena; Stevović, Vladeta; Bošković-Rakočević, Ljiljana; Moravčević, Đorđe; Poštić, Dobrivoj; Zdravković, Jasmina (Food and Feed Research, 2021)
The demand for organic food is rising since consumers want food from reliable, highest quality sources originating from the environment, undisturbed by cultivation and processing. It is necessary to determine to what extent there is a scientific basis for the claims that organic food is of high quality. In this study, beetroot from an organic production system originating from 6 certified organic food producers from different geographic locations was examined. The organic beetroot samples were processed by pasteurization at 700 C and 900 C into beet juice or by drying at 550 C. The following samples were tested and compared: fresh beetroot, pasteurized beet juice and dried beetroot slices. The concentration of vitamin C, level of total phenol compounds (TPC) and antioxidative activity (TAA) in beetroot were influenced by the geographic origin and the applied processing method. The highest degradation for all analysed parameters was found in the samples treated by drying or pasteurisation at 90ºC. The lowest losses of studied phytochemical components were observed during juice pasteurisation at 700C. The correlation coefficient between TPC and TAA was high and significant (r2 = 0.966).
Keywords: pasturization; juice; drying; phytochemicals; degradation; geographic origin